2018
DOI: 10.1155/2018/3050537
|View full text |Cite
|
Sign up to set email alerts
|

Excision and Primary Anastomosis for Short Bulbar Strictures: Is It Safe to Change from the Transecting towards the Nontransecting Technique?

Abstract: Objective To explore whether it is safe to change from transecting excision and primary anastomosis (tEPA) towards nontransecting excision and primary anastomosis (ntEPA) in the treatment of short bulbar urethral strictures and to evaluate whether surgical outcomes are not negatively affected after introduction of ntEPA. Materials and Methods Two-hundred patients with short bulbar strictures were treated by tEPA (n=112) or ntEPA (n=88) between 2001 and 2017 in a single institution. Failure rate and other surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…introduced the vessel-sparing or nontransecting EPA,[ 55 ] which was modified by Andrich and Mundy[ 56 57 ] and has been incorporated into clinical practice. [ 58 59 60 61 ] To date, however, there is no clear evidence of a superiority of the nontransecting approach over conservative transecting EPA regarding postoperative sexual and erectile functions,[ 61 ] but both approaches appear to be equally effective regarding stricture recurrence-free survival and perioperative safety. [ 59 60 61 ]…”
Section: Disease Managementmentioning
confidence: 99%
“…introduced the vessel-sparing or nontransecting EPA,[ 55 ] which was modified by Andrich and Mundy[ 56 57 ] and has been incorporated into clinical practice. [ 58 59 60 61 ] To date, however, there is no clear evidence of a superiority of the nontransecting approach over conservative transecting EPA regarding postoperative sexual and erectile functions,[ 61 ] but both approaches appear to be equally effective regarding stricture recurrence-free survival and perioperative safety. [ 59 60 61 ]…”
Section: Disease Managementmentioning
confidence: 99%
“…Promising short-term results have been described in single-arm observational studies and are in line with the reported composite success rate of the ICUD [ 3 , 6 10 ]. However, direct comparisons between vsAR and tAR have only been done in retrospective studies which are strongly biased by the fact that patients who underwent vsAR had shorter follow-up than patients who underwent tAR [ 11 , 12 ]. Moreover, since vsAR is a more novel technique, one could hypothesize that the performing surgeon is better trained and more experienced in the era of vsAR compared to the earlier in their surgical career, when tAR was the only AR technique.…”
Section: Introductionmentioning
confidence: 99%